THE ROLE OF ORGANIC SUBSTANCES IN STIMULATING THE ACTIVITIES OF SOIL MICROORGANISMS (Scientific journal of the Fergana State University, 2025)
This article studies the application of 2 or 14 t/ha of chopped guza-pai, 30 t/ha of manure and their various combinations under alfalfa sowing, as a result, a positive effect on the number of bacteria is established: an increase (by 17,0-63,5), fungi (by 0,5-4,4), actinomycetes (by 1,0-6,0), i.e. an improvement in the biological activity of the soil, and therefore an increase in its immunity to phytopathogens.